Analysis of Decision No. 568/Pdt.G/2020 on Arrears of Maintenance in a Divorce Lawsuit from the Perspective of Islamic Law - Zainal Arifin; Puput Alifah; Nashih Muhammad; Sumarjoko (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study examines the Decision of the Temanggung Religious Court No. 568/Pdt.G/2020/PA.Tmg concerning arrears of maintenance in a divorce lawsuit, which arises from household problems caused by the husband’s neglect of maintenance obligations during a period of living separately. Economic difficulties constitute the dominant factor triggering marital conflict and ultimately leading to divorce, thereby giving rise to the wife’s claim for arrears of maintenance. This research aims to analyze the judges’ legal considerations in deciding the case and to assess their conformity with the principles of Islamic law. The research method employed is a normative–juridical approach, with data collected through library research on court decisions, statutory regulations, the Compilation of Islamic Law, legal doctrines, and relevant Islamic legal literature. Data analysis is conducted using a descriptive–qualitative method by examining legal norms and judicial considerations.The findings indicate that maintenance is positioned as a husband’s obligation that does not lapse despite living separately, and failure to fulfill this obligation results in legal consequences in the form of arrears of maintenance that may be claimed by the wife. This decision is in line with the principles of justice in Islamic law and strengthens the protection of the wife’s economic rights. This study is expected to contribute to the development of Islamic family law studies and to increase public awareness of the importance of maintenance responsibilities within the household